Economic Growth, Energy Consumption and Human Capital Formation: Implication for Knowledge-based Economy - Olopade, Bosede Comfort; Okodua, Henry; Oladosun, Muyiwa; Matthew, Oluwatoyin; Urhie, Ese; Osabohien, Romanus; Adediran, Oluwasogo; Johnson, Olubunmi H. (International Journal of Energy Economics and Policy, 2019)
This study examines the relationship between technology, human capital and economic growth and also attempts to establish their implications on knowledge based economy in Nigeria. The data used for the study are from secondary sources while the new growth model was also adopted. The dependent variable in the model is the level of real output while the explanatory variables are gross capital formation and government expenditure on education. The result of the causality test shows that is a uni-directional relationship running from gross capital formation and real output, human capital formation and real output growths do not Granger cause each other while causality runs from human capital to capital formation and vice versa. The implication of the result; the increase in economic growth has not improve the rate of capital formation in Nigeria. The study concluded that Nigeria has been slow to identify the strands of global knowledge due to the following: weak institutions; limited awareness and disincentives preventing them from taking the root to the knowledge and information based- economy. Based on the findings the study recommended; strategies in which education can be incorporated into the growth system. Research and development should be encouraged as well and polices that promote output through savings. Keywords: Economic Growth, Human Capital Formation, Knowledge and Information Based Economy, Technology. JEL Classifications: O47, O15, G14 DOI: https://doi.org/10.32479/ijeep.8165